Optimal Timing of P2Y12 Inhibitor Loading in Patients Undergoing PCI: A Meta-Analysis - Komosa, Anna; Lesiak, Maciej; Krasiński, Zbigniew; Grygier, Marek; Siniawski, Andrzej; Skorupski, Włodzimierz; Olasińska-Wiśniewska, Anna; Pyda, Małgorzata; Araszkiewicz, Aleksander; Mitkowski, Przemysław; Grajek, Stefan; Mularek-Kubzdela, Tatiana; Hengstenberg, Christian; Siller-Matula, Jolanta M. (Thrombosis and Haemostasis, 2019)
Background and Aim The timing of P2Y12 inhibitor loading in patients undergoing percutaneous coronary intervention (PCI) is a matter of debate. The aim of our study was to compare the efficacy and safety of oral P2Y12 inhibitors: clopidogrel, ticagrelor and prasugrel administered at two different time points in relation to PCI: early (> 2 hours pre-PCI) versus late (< 2 hours pre-PCI or post-PCI).Methods This is a systematic review and meta-analysis. Randomized controlled trials and non-randomized studies were included. Outcomes evaluated were combined major adverse cardiovascular events (MACEs), myocardial infarction (MI), target vessel revascularization, death and bleeding complications. Summary estimates of the relative risks with therapy were calculated.Results Twenty-three studies met the selection criteria and included 60,907 patients. Early P2Y12 inhibitor loading was associated with a 22% relative risk reduction (RRR) of MACE (95% confidence interval [CI] = 0.68–0.89; p < 0.001). Early clopidogrel loading was associated with a 25% RRR of MACE (95% CI = 0.65–0.85; p < 0.001), a 30% RRR of MI (95% CI = 0.6–0.82; p < 0.0001) and 25% RRR of death (95% CI = 0.64–0.87; p = 0.0002), without an impact on major bleedings. In ST-elevation myocardial infarction as well as non-ST elevation acute coronary syndrome (NSTE-ACS), early clopidogrel loading resulted in 35 and 22% RRR in 30 days MACE (p < 0.001), respectively, with no impact in elective PCI. Whereas early loading with prasugrel and ticagrelor did not improve ischaemic outcomes, prasugrel administered early increased bleeding risks in NSTE-ACS.Conclusion Early clopidogrel loading is associated with a better efficacy and similar safety, whereas timing of ticagrelor or prasugrel loading had no effects on ischaemic events.
Keywords: clopidogrel; prasugrel; ticagrelor; P2Y12 inhibitor; timing